Leptin‐induced migration and angiogenesis in rheumatoid arthritis is mediated by reactive oxygen species. Issue 12 (6th November 2017) - Sun, Xiaotong; Wei, Jing; Tang, Yawei; Wang, Bing; Zhang, Yan; Shi, Lei; Guo, Jianping; Hu, Fanlei; Li, Xia
Abstract : Rheumatoid arthritis (RA) is a progressive autoimmune disease affecting the joints. In this study, we investigated the role of the pro‐angiogenic factor leptin in regulating reactive oxygen species (ROS) to promote cell migration and angiogenesis in RA. We showed that leptin triggered RA fibroblast‐like synoviocyte (FLS) migration by increased ROS expression. Additionally, leptin enhanced human umbilical vein endothelial cell (HUVEC) tube formation in a ROS/hypoxia‐inducible factor‐1α‐dependent manner, accompanied by increased production of vascular endothelial growth factor and interleukin (IL)‐6. We also revealed that antagonists of tumor necrosis factor, IL‐6 and IL‐1β down‐regulated ROS production of RA FLS induced by leptin, which subsequently attenuated RA FLS migration and HUVEC tube formation. These findings demonstrated that leptin might play an important role in RA FLS migration and HUVEC angiogenesis. Abstract : Rheumatoid arthritis (RA) is a progressive autoimmune disease affecting the joints. In this study, we showed that the pro‐angiogenic factor leptin triggered the migration of fibroblast‐like synoviocytes by increasing production of reactive oxygen species (ROS). Leptin also enhanced human umbilical vein endothelial cell tube formation in a ROS/hypoxia‐inducible factor (HIF)‐1α‐dependent manner. These results suggest that leptin might be a critical factor in the pathogenesis of RA.